2014
DOI: 10.1021/bm500229d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cellulose Nanocrystals Carrying Tyrosine Sulfate Mimetic Ligands and Inhibition of Alphavirus Infection

Abstract: We present two facile approaches for introducing multivalent displays of tyrosine sulfate mimetic ligands on the surface of cellulose nanocrystals (CNCs) for application as viral inhibitors. We tested the efficacy of cellulose nanocrystals, prepared either from cotton fibers or Whatman filter paper, to inhibit alphavirus infectivity in Vero (B) cells. Cellulose nanocrystals were produced by sulfuric acid hydrolysis leading to nanocrystal surfaces decorated with anionic sulfate groups. When the fluorescent mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 49 publications
3
78
0
Order By: Relevance
“…The reports available in the literature to date are summarized in Table 2. 25,[48][49][50][51][52][53][54][55][56][57] Most studies showed CNCs to have no cytotoxic effects, as defined by ISO standard 10993-5, i.e., not to reduce cell viability by more than 30%. However, several studies found a dose dependency of CNC cytotoxicity.…”
Section: Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The reports available in the literature to date are summarized in Table 2. 25,[48][49][50][51][52][53][54][55][56][57] Most studies showed CNCs to have no cytotoxic effects, as defined by ISO standard 10993-5, i.e., not to reduce cell viability by more than 30%. However, several studies found a dose dependency of CNC cytotoxicity.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…However, several studies found a dose dependency of CNC cytotoxicity. 25,49,53,56,57 The most pronounced decrease in cell viability was reported by Kovacs et al, who reported a decrease in rainbow trout hepatocyte viability of 20% at an estimated CNC concentration of 0.034 mg/ mL and a decrease of 50%, i.e., cytotoxic effects at an estimated concentration of 0.245 mg/mL. 49 The results of Kovacs et al are in stark contrast to the findings of a more recent study by Zoppe et al, who reported human corneal epithelial cell viabilities in excess of 90% at a CNC concentration of 0.1% (*1 mg/mL).…”
Section: Cytotoxicitymentioning
confidence: 99%
“…This peak was observed in all samples due to the presence of hydroxyl groups in cellulose, hemicelluloses, and lignin (Zoppe et al 2014;Lamaming et al 2015). Bands between 2904 and 2921 cm −1 (section B) were assigned to saturated aliphatic C-H stretching characteristics of methylene groups in cellulose (Habibi et al 2010).…”
Section: Ftirmentioning
confidence: 90%
“…The term CNW is used for materials such as cellulose nanocrystals (CNC), nanocrystalline cellulose (NCC), and cellulose crystallites (CC) (Zoppe et al 2014;Brioude et al 2015). CNW are highly crystalline needle-shaped cellulose particles with one of its dimensions equal to or less than 100 nm (Sebe et al 2012;Chen et al 2014;Xu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Considering these results and the chemical structure of other known polyanionic inhibitors, the possibility to using CNCs for inhibition of other viruses (e.g., HIV and herpes simplex viruses) should be explored. 55 A recent work also reported the production of nanocrystals of a reverse transcriptase inhibitor from HIV-1 virus (CSIC) by a three-phase nanoparticle engineering technology for intravaginal delivery. 56 During the last decade, investigations have shown the potential of metal nanoparticles for treatment of viral infections.…”
Section: Antiviral Drugsmentioning
confidence: 99%